Determining if Telehealth Can Reduce Health System Costs: Scoping Review - Snoswell, Centaine L; Taylor, Monica L; Comans, Tracy A; Smith, Anthony C; Gray, Leonard C; Caffery, Liam J (JMIR Publications, 2020)
BackgroundTelehealth represents an opportunity for Australia to harness the power of technology to redesign the way health care is delivered. The potential benefits of telehealth include increased accessibility to care, productivity gains for health providers and patients through reduced travel, potential for cost savings, and an opportunity to develop culturally appropriate services that are more sensitive to the needs of special populations. The uptake of telehealth has been hindered at times by clinician reluctance and policies that preclude metropolitan populations from accessing telehealth services. ObjectiveThis study aims to investigate if telehealth reduces health system costs compared with traditional service models and to identify the scenarios in which cost savings can be realized. MethodsA scoping review was undertaken to meet the study aims. Initially, literature searches were conducted using broad terms for telehealth and economics to identify economic evaluation literature in telehealth. The investigators then conducted an expert focus group to identify domains where telehealth could reduce health system costs, followed by targeted literature searches for corresponding evidence. ResultsThe cost analyses reviewed provided evidence that telehealth reduced costs when health system-funded travel was prevented and when telehealth mitigated the need for expensive procedural or specialist follow-up by providing competent care in a more efficient way. The expert focus group identified 4 areas of potential savings from telehealth: productivity gains, reductions in secondary care, alternate funding models, and telementoring. Telehealth demonstrated great potential for productivity gains arising from health system redesign; however, under the Australian activity-based funding, it is unlikely that these gains will result in cost savings. Secondary care use mitigation is an area of promise for telehealth; however, many studies have not demonstrated overall cost savings due to the cost of administering and monitoring telehealth systems. Alternate funding models from telehealth systems have the potential to save the health system money in situations where the consumers pay out of pocket to receive services. Telementoring has had minimal economic evaluation; however, in the long term it is likely to result in inadvertent cost savings through the upskilling of generalist and allied health clinicians. ConclusionsHealth services considering implementing telehealth should be motivated by benefits other than cost reduction. The available evidence has indicated that although telehealth provides overwhelmingly positive patient benefits and increases productivity for many services, current evidence suggests that it does not routinely reduce the cost of care delivery for the health system.